GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Brain concentrations of flame retardants and trace elements related to habitat use and brain measures in an urban-adapted gull - Anna Lippold; Mélanie F. Guigueno; Marilou Lalumière; Chavy Dworkind; Alison Aube; Amy Smith-Dijak; Brenda Toscano-Marquez; Anna A. Cook; Alanna J. Watt; Jonathan Verreault (Environmental Pollution, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Upregulation of NLRP3 Inflammasome in Specific Hippocampal Regions: Strengthening the Link Between Neuroinflammation and Selective Vulnerability in Alzheimer’s Disease - Eliana C. B. Toscano; Alberto F. O. Justo; Michelle C. A. Paula; Laura B. Grossi; Vitor H. Neves; Renata E. P. Leite; Vitor R. Paes; Rossana C. N. Melo; Ricardo Nitrini; Carlos Pasqualucci; Eduardo Ferriolli; Antonio L. Teixeira; et al. (Molecular Neurobiology, 2025)

Integrating UAV hyperspectral imaging with machine learning techniques to predict tomato ecophysiological parameters and yield - A. Matese; N. Hamie; S. Baronti; A. Berton; R. Dainelli; P. Toscano; F. Ugolini; S. F. Di Gennaro (Precision Agriculture, 2025)

Tissue-specific energetics of the invasive Asian shore crab Hemigrapsus sanguineus throughout its range and through time - Blaine D. Griffen; Laura S. Fletcher; Tanner C. Reese; Michele F. Repetto; Nanette Smith; Carter K. Stancil; Benjamin J. Toscano (Oecologia, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Factors influencing variation in reproduction in invasive species: a case study of the Asian shore crab Hemigrapsus sanguineus - Blaine D. Griffen; Mikayla Bolander; Laura S. Fletcher; Johanna Luckett; Michele F. Repetto; Nanette Smith; Carter Stancil; Benjamin J. Toscano (Biological Invasions, 2024)
Reproductive success is a strong determinant of invasive species success. It is common for studies on invasive species to assess reproduction by measuring size-specific fecundity and scaling this up using population size or densities. Yet, reproductive success is influenced by numerous factors that are not accounted for in such calculations. We examined the influence of several factors on fecundity (clutch size) and egg size in the Asian shore crab Hemigrapsus sanguineus , including body size, spatial variation throughout the invaded range, season, fertilization success, brood loss, and diet. We show that all of these factors influence reproduction simultaneously within the invaded North American range of this species, though the relative importance of these different factors varied across sites or sampling times. Our study demonstrates that numerous factors may influence the reproductive success of invasive species and that studies that rely on fecundity measured at a single place and time, or that ignore factors such as offspring quality or brood loss, may provide a skewed picture of reproduction, and thus of potential invasive success.

Spatial variability of fine particle number concentration in an urban area: The effect of aspect ratio and vehicular traffic - F. Murena; D. Toscano (Urban Climate, 2023)

Development of point sampling technology for identifying high-emitting vehicles in narrow and deep street canyons - F. Murena; D. Toscano (Atmospheric Pollution Research, 2023)

Beneficial effects of selected rhizospheric and endophytic bacteria, inoculated individually or in combination, on non-native host plant development - Alejandro Méndez-Bravo; Lorena C. Herrera-Cornelio; Daniel F. García-Toscano; Ana L. Kiel-Martínez; Edgar Guevara-Avendaño; Mónica Ramírez-Vázquez; Yareli Pérez-Bautista; Alfonso Méndez-Bravo; Frédérique Reverchon (Rhizosphere, 2023)

Realizing the potential of trait‐based aquatic ecology: New tools and collaborative approaches - Colin T. Kremer; Alicia K. Williams; Michael Finiguerra; Allison A. Fong; Anne Kellerman; Sara F. Paver; Bradley B. Tolar; Benjamin J. Toscano (Limnology and Oceanography, 2017)
Trait‐based ecology, which focuses on using the traits of species and individuals to understand ecology (from populations to ecosystems), is becoming an increasingly productive and widely employed paradigm. To date, trait‐based approaches have been used to study taxa from microbes to megafauna in every major area of aquatic ecology yielding exciting results. However, this promising field faces a number of significant obstacles, including: (1) identifying and measuring ecologically relevant traits, (2) integrating inter‐ and intra‐specific trait variation, (3) detecting and quantifying trait correlations and trade‐offs, and (4) accounting for the context dependency of traits. These issues are often particularly acute for specific taxa or systems. This paper highlights these looming challenges, as well as ways to address them. Proposed solutions center around using new technologies to collect trait data, coordinating research efforts, and curating and sharing data. Throughout, we take an interdisciplinary approach, sharing examples spanning a wide range of aquatic taxa and systems. It is our hope that this paper will stimulate frank discussions and help the growing field of trait‐based aquatic ecology maximize its potential.

An assessment of contamination of the Fusaro Lagoon (Campania Province, southern Italy) by trace metals - M. Arienzo; F. Toscano; M. Di Fraia; L. Caputi; P. Sordino; M. Guida; F. Aliberti; L. Ferrara (Environmental Monitoring and Assessment, 2014)

Distribution of heavy metals and pollution pathways in a shallow marine shelf: assessment for a future management - F. Ruiz; M. L. González-Regalado; J. M. Muñoz; M. Abad; A. Toscano; M. I. Prudencio; M. I. Dias (International Journal of Environmental Science and Technology, 2014)

Aircraft mass budgeting to measure CO2 emissions of Rome, Italy - Beniamino Gioli; Maria F. Carfora; Vincenzo Magliulo; Maria C. Metallo; Attilio A. Poli; Piero Toscano; Franco Miglietta (Environmental Monitoring and Assessment, 2014)

Freshwater ostracods as environmental tracers - F. Ruiz; M. Abad; A. M. Bodergat; P. Carbonel; J. Rodríguez-Lázaro; M. L. González-Regalado; A. Toscano; E. X. García; J. Prenda (International Journal of Environmental Science and Technology, 2013)

New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.

Age and depositional environment of the Draa Sfar massive sulfide deposit, Morocco - C. Moreno; R. Sáez; F. González; G. Almodóvar; M. Toscano; G. Playford; A. Alansari; S. Rziki; A. Bajddi (Mineralium Deposita, 2008)

Influence of Seasonal Nitrogen Nutrition Fluctuations in Orange and Lemon Trees on Population Dynamics of the Glassy-Winged Sharpshooter (Homalodisca coagulata) - J. L. Bi; S. J. Castle; F. J. Byrne; S. J. Tuan; N. C. Toscano (Journal of Chemical Ecology, 2005)